1991
DOI: 10.1111/j.1471-4159.1991.tb02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Neurochemical Interactions of Tiletamine, a Potent Phencyclidine (PCP) Receptor Ligand, with the N‐Methyl‐D‐Aspartate‐Coupled and ‐Uncoupled PCP Recognition Sites

Abstract: Neurochemical interactions of tiletamine, a potent phencyclidine (PCP) receptor ligand, with the N-methyl-D-aspartate (NMDA)-coupled and -uncoupled PCP recognition sites were examined. Tiletamine potently displaced the binding of [3H]1-(2-thienyl)cyclohexylpiperidine with an IC50 of 79 nM without affecting sigma-, glycine, glutamate, kainate, quisqualate, or dopamine (DA) receptors. Like other PCP ligands acting via the NMDA-coupled PCP recognition sites, tiletamine decreased basal, harmaline-, and D-serine-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
2
12
1
Order By: Relevance
“…However, following intracerebroventricular administration (100-500 µg/rat), tiletamine increased pyriform cortical DA metabolism with a bell-shaped dose-response curve. This indicates that there is activation of either a different receptor or a neuronal pathway of unknown pharmacology [5]. Our results are in accordance with these findings since treatment with zoletile mixture did not affect the binding of [ 125 I]PE2I or [ 3 H]-(S)-citalopram, whereas ketamine/xylazine did.…”
Section: Zoletile Mixturesupporting
confidence: 91%
“…However, following intracerebroventricular administration (100-500 µg/rat), tiletamine increased pyriform cortical DA metabolism with a bell-shaped dose-response curve. This indicates that there is activation of either a different receptor or a neuronal pathway of unknown pharmacology [5]. Our results are in accordance with these findings since treatment with zoletile mixture did not affect the binding of [ 125 I]PE2I or [ 3 H]-(S)-citalopram, whereas ketamine/xylazine did.…”
Section: Zoletile Mixturesupporting
confidence: 91%
“…It should be stressed, however, that CGP 40116 was effective only at doses which evoked a behavioural (Koek and Colpaert 1990;K o e k et al 1988;L6scher et al 1993;Willetts et al 1990). The observed effects are in contrast to a n u m b e r of data published previously, which failed to demonstrate any effects of competitive N M D A antagonists on the dopaminergic neurotransmission (Bubser et al 1992;K a b u t o et al 1989;Rao et al 1990Rao et al , 1991Svensson et al 1991). At the level of DA metabolism, depending on the applied doses, both drugs, increase the concentration of DA only, or the concentration of DA, D O P A C and HVA.…”
Section: Discussioncontrasting
confidence: 96%
“…Involvement of dopamine (DA) in the above side-effects has been confirmed by studies, which indicate that drugs operating via dopaminergic receptors antagonize some behavioural effects of MK-801 (Maj et al 1991;Wolf et al, 1993). In contrast to MK-801, which coherently enhances the dopaminergic neurotransmission, preliminary data have shown that competitive NMDA antagonists such as AP-5, AP-7, CPP, D-CPPene, CGP 39551, CGP 37849 and CGS 19755 are devoid of effects on dopaminergic neurotransmission (Bubser et al 1992;Kabuto et al 1989;Rao et al 1990Rao et al , 1991Svensson et al 1991), which in turn, is interpreted as evidence for a possible lack of DA-dependent psychotomimetic and abusing PCP-like sideeffects. These initial data, however, seem to disagree with some behavioural observations which indicate that, when given in doses higher than these antagonizing the effects of NMDA, competitive NMDA antagonists might induce effects typical of PCP, such as stereotyped behaviour and locomotion-stimulating effects (Koek and Colpaert 1990;Koek et al 1988;LSscher and Honack 1991a,b;Willetts et al 1990), which, in consequence suggest that at a certain range of doses also competitive NMDA antagonists may evoke PCP-like, undesired side-effects, possibly via a similar mechanism (Willetts et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Tiletamine (2-(ethylamino)-2-(2-thienyl)-cyclohexanone, or CI-634) is a non-competitive N-methyl-D-aspartate (NMDA) receptor antagonist chemically related to ketamine and phencyclidine (PCP) (Chapman and Meldrum, 1989;Olney et al, 1989;Rao et al, 1991a).…”
Section: Introductionmentioning
confidence: 99%
“…Presently listed as a Schedule III controlled substance, tiletamine causes dose-dependent ataxia and motor stereotypies in animals (Rao et al, 1991a), also demonstrating abuse potential in both experimental (de la Pena et al, 2012;de la Pena et al, 2013) and clinical studies (Morris and Wallach, 2014;Quail et al, 2001).…”
Section: Introductionmentioning
confidence: 99%